FORMULASI DAN EVALUASI FISIK SEDIAAN SERUM WAJAH LENDIR BEKICOT (Achatina fulica) DENGAN VARIASI KONSENTRASI XANTHAN GUM SEBAGAI GELLING AGENT - Dian Nurul Hidayah; Iin Suhesti; Ester Dwi Antari (Program Studi D3 Farmasi Politeknik Indonusa Surakarta, 2022)
Snail slime (Achatina fulica) has a strong inhibitory power against Propionibacterium acnes bacteria, this is because snail mucus has an active compound achasin. This study aims to determine the formulation and physical evaluation of serum and effect of variations in the concentration of xanthan gum as a gelling agent. In this research method used qualitative experiments with variations in the concentration of xanthan gum, namely F1 = 0,25%, F2 = 0,50%, F3 = 0,75%. The results of the third organoleptic test have almost the same shape, smell and color, semi-solid, odorless and album white in color. The homogeneity test shows that the three formulas are homogeneous. The resultof the evaluation of facial serum pH is F1=4,56±0,05; F2=4,96±0,05; F3=4,97±0,03 met the requirements for a good facial serum pH of 4,50-6,50. The results of the dispersion test at F1=6,83±0,01cm; F2=6,78±0,03cm; F3=6,72±0,02cm fulfills the requirements for the dispersion test, which is 5-7cm. Viscosity test results F1=544,82±23,17cPs; F2=5.568,70±280,26cPs; F3=10.326±219,54cPs indicates that only F1 meets the requirements for a good serum viscosity of 230-1150cPs. Transferred volume test results F1=97,44±0,01; F2=95,67±0,50; F3 = 95,33±0,50 meets the requirements. The results of the hedonic test were F1 the most preferred based on the color and aroma categories and F2 the most preferred based on the color and texture categories. Based on the results of statistical tests using One Way ANOVA and Kruskal-Wallis, it can be ascertained that variations in the concentration of xanthan gum have no effect on the results of physical evaluation